Recognizing The Children English Vocabulary Input Through Internet - Adhi Kusuma; Victa Sari Dwi Kurniati (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2020)
It cannot be denied that children nowadays are very familiar with Internet. They mostly use internet connection for playing games rather than supporting their school assignments. Most online games the children play are imported from abroad so that language used is mostly English. As a result, children frequently pick up many English words from the game naturally. The present study is the continuous study of the vocabulary learning strategy mapping among 28 primary school students on grade 5 using the VOLSQUES survey. From the survey, the researcher found that 29% respondents chose internet as the source of their English vocabulary input. Started from this finding, the researcher continue the study by conducting descriptive qualitative research on those 29% respondents. The focus is on recognizing the Internet content commonly the respondents use and type of English vocabulary input they gain. All the respondents admit that they frequently play online games, especially the Mobile Legend game. The interesting result is that the participants are mostly unable to read and write the English words they recognize from the game correctly. This is understandable since the children listen from the game narrators. Besides, the typical English words they acquire are instructions.